Estamos en constante cambio y siempre mejorando (VITAL, 2025)
The Faculty of Medicine is constantly renewing itself. The renovation of classrooms and University Wellness areas at the Circunvalar campus has been completed, including spaces for meditation and a gym. Block 1 was also renovated, featuring new offices, meeting rooms, and study areas. Additionally, a Primary Healthcare Ambulatory Center is planned for the Vívelo Mercurio Shopping Center in Soacha (Bogotá). This center will offer various low-cost services and provide opportunities for graduates, strengthening the accreditation process.